2006
DOI: 10.1007/s10439-005-9008-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Intracellular Organization and Functional Architecture Mediating Cellular Behavior

Abstract: Abstract-Cells function based on a complex set of interactions that control pathways resulting in ultimate cell fates including proliferation, differentiation, and apoptosis. The interworkings of this immensely dense network of intracellular molecules are influenced by more than random protein and nucleic acid distribution where their interactions culminate in distinct cellular function. By probing the design of these biological systems from an engineering perspective, researchers can gain great insight that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 112 publications
0
24
0
Order By: Relevance
“…Syndecan-4 molecules have been shown to indirectly attach to primary protein components of the FAC, including paxillin, that is linked to the actin cytoskeleton (16). In addition, studies have already indicated that heparin sulfate-linked proteins could have a role in mechanical signaling (15) and have been implicated in numerous processes from cell signaling to adhesion (18). Furthermore, in tests of mechanotransduction using integrin-based adhesion, syndecans are known to cluster at the FAC, potentially implicating them in this pathway and reinforcing their interrelationship to the process of mechanical activation (19).…”
mentioning
confidence: 99%
“…Syndecan-4 molecules have been shown to indirectly attach to primary protein components of the FAC, including paxillin, that is linked to the actin cytoskeleton (16). In addition, studies have already indicated that heparin sulfate-linked proteins could have a role in mechanical signaling (15) and have been implicated in numerous processes from cell signaling to adhesion (18). Furthermore, in tests of mechanotransduction using integrin-based adhesion, syndecans are known to cluster at the FAC, potentially implicating them in this pathway and reinforcing their interrelationship to the process of mechanical activation (19).…”
mentioning
confidence: 99%
“…One of the major motivations for the increasing effort spent on designing and developing nanostructured materials for TE strategies is that natural tissues and the associated extracellular matrices are in fact composed of nanostructured materials [3,69,104] ( Fig. 1.2).…”
Section: The Need For Micro and Nanotechnologies In Tissue Engineerinmentioning
confidence: 99%
“…Down to the single-cell level, it is known that the fulfillment of cell functions is based on a complex set of molecular interactions which control signaling pathways to influence ultimate cell fates, including proliferation, differentiation, and apoptosis. 12 These molecular interactions predominate at the nanoscale. 13 Therefore, in principle, in order to thoroughly understand the underlying mechanisms guiding cellular behaviors, directly observing molecular activities taking place at the nanoscale is indispensable.…”
Section: Introductionmentioning
confidence: 99%